Projected climate change impacts on crop yields in China's drylands by statistical models and emulators - Shuangshuang Zi; Yiqing Liu; Yan Li; Shuai Wang; Shan Sang; Huiqing Lin; Chengcheng Hou; Fengyu Fu; Bojie Fu (Agricultural Systems, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Laser pyrolysis of poly(methyl methacrylate) to high-yield and high-purity methyl methacrylate monomer: A solvent- and catalyst-free strategy for chemical recycling - Xu-Zhen Zhu; Guang-Jian He; Meng-Meng Wang; Fu-Lu Chang; Zi-Yang Hua; Hao-Bo Wang; Xuan-Qi Wu; Lun Chen (Chemical Engineering Journal, 2026)

MXene hollow microspheres with tunable sizes and heterostructures for high-efficiency broadband microwave absorption - Yan-Qin Wang; Lin Zhang; Hao Chen; Zi-Hao Wang; Fu-Rong Zeng; Hai-Bo Zhao (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Preparation and performance analysis of a novel composite dust suppressant considering wind and train vibration effects - Hao-kui Wang; Ming-yi Chen; Zi-ting Pei; Fu-chao Tian; Yue Ren; Xing-jun Ma; Ming-xin Li (Journal of Environmental Chemical Engineering, 2026)

β-Cyclodextrin-mediated co-encapsulation of peptide PPHG and gallic acid: Synergistic thrombin-inhibitory activity, enhanced stability, and sustained simulated gastrointestinal release - Zi-Han Qu; Zi-Han Liu; Xue-Fu Li; Hai-Bin Ren; Di-Feng Ren; Jun Lu (Food Bioscience, 2026)

Microscopic deformation mechanism of clay aggregates in view of the montmorillonite particles rearrangements under cyclic loading-unloading conditions - Zi-Yu Ding; Kai-Wen Tong; Yong-Gui Chen; Qiong Wang; Wen-Jie Dai; Xing-Guang Zhao; Chang-Fu Wei; Zhi-Jun Zhang (Applied Clay Science, 2026)

Study on the identification, generation mechanism and coloring effect of 5,7-dihydroxycoumarin formed from the autoxidation of EGCG - Zi-Xin Zhao; Zhuo-Shun Dai; Jie-Qiong Wang; Jun-Feng Yin; Liang Zhang; Yong-Quan Xu; Yan-Qing Fu (Food Chemistry, 2026)

Enhanced power factor n-type carbon nanotube thermoelectric films enabled by liquid-crystal ordering for self-powered encrypted signal sensing - Qing-Yi Ma; Wen-Qian Leng; Zi-Yan Li; Fei-Peng Du; Ping Fu; Chak-Yin Tang; Chi-Pong Tsui; Wing-Cheung Law; Yun-Fei Zhang (Chemical Engineering Journal, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

MFN2-mediated remodelling of ER-mitochondria communication alleviates ochratoxin A-induced hepatocyte ferroptosis by enhancing mitophagy - Zi-Yan Hu; Rui-Qi Liu; Yu-Xuan Ouyang; Ming-Shan Chen; Jia-Xin Wang; Ming Lou; Yi-Feng Huang; Hong-Li Si; Fu-Wei Jiang; Zhuo-Yu Liu; Yi-Bo Wang; Li Wang; et al. (Journal of Hazardous Materials, 2026)

Deletion of electron-bifurcating [FeFe]-hydrogenase enhances H2-driven CO2 fixation and ethanol production in Clostridium ljungdahlii - Zhi-Qiong Wen; Yu-Zhen Li; Hai-Jia Su; Jun-Zhe Zhang; Zi-Yong Liu; Shu-Ning Wang; Hui Wang; Fu-Li Li; Xiao-Qing Ma (Bioresource Technology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Dominant role of N2O5 hydrolysis in nitrate formation on mineral dust: insights from size-resolved dual isotopes - Weijie Huang; Xingnan Ye; Bingyue Fu; Yinghui Yao; Zi Li; Jianmin Chen (Journal of Environmental Sciences, 2026)

Autotetraploid induction and one-step regeneration, and transcriptomic analysis in Dendrobium officinale - Cong-Dan Zheng; Jun-Yu Su; Shang-Yan Fu; Jie-Mei Deng; Zi-Ting Zhu; Heng-Yu Huang; Yuan-Zhong Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Centralized mechanical e-waste dismantling is associated with lower farmland soil heavy metal pollution and carbon emission intensity - Yu Zhang; Ming-jiang He; Wei-jun Fu; Jie Wang; Ke-li Zhao; Xiang-rui Xu; Ji-zi Wu (Journal of Environmental Chemical Engineering, 2026)

Functional characterization of chemosensory proteins in Pharsalia antennata with special emphasis on the roles of CSP2 orthologs in pheromone detection - Fu-Peng Li; Xiao-Rong Xiong; Zi-Hui Liu; Zi-Hao Long; Lin-Mei Pu; Nai-Yong Liu (Insect Biochemistry and Molecular Biology, 2026)

Decoupling of Fe isotope and Fe3+/ΣFe in arc igneous rocks: Implications for crustal metasomatism and its contribution to mantle redox - Li-Tao Ma; Li-Qun Dai; Zi-Wei Yao; Zi-Fu Zhao; Ye-Dan Hu; Zhen-Wu Chen; Guo-Chao Sun (Geochimica et Cosmochimica Acta, 2026)

Whole-rock Mg isotopes distinguishing high- and low-temperature S-type granites - Yan Wang; Peng Gao; Zi-Fu Zhao; Hai-Ou Gu; Guo-Chao Sun; Hui-Chan Huang; Zhang-Jian Wu; Changqing Yin (Geochimica et Cosmochimica Acta, 2026)

The dual origin of granites from fluid-absent and fluid-fluxed melting of the juvenile lower crust: New constraints from Mo isotopes and phase equilibrium modeling - You-Shan Xia; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Yao Zhou; Zhen-Xin Li; Gang Wen; Lei Qin (Geochimica et Cosmochimica Acta, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Molybdenum isotopes in metamorphic and magmatic rocks may record substantial fluid activity in continental subduction zones - Wei Fang; Li-Qun Dai; Ren-Xu Chen; Zi-Fu Zhao (Chemical Geology, 2026)

Study on the synergistic efficacy and mechanism of CD24 silencing combined with trastuzumab in HER2-positive breast cancer - Yi Lu; Xinglu Zhou; Yue Gao; Zi Zhu; Bao Deng; Wubin Lv; Zhenkun Fu; He Ding; Lei Zhong (Journal of Molecular Histology, 2026)

Effect of high-pressure homogenization on surfactant-free starch-oil films - Xi-ying Xu; Dong-ming Gao; Xu Yao; Zi-xu Zheng; Zong-qiang Fu; Gang Li; Fei-fei Li (Journal of Food Engineering, 2026)

Large-scale gold incorporation in bulk pyrite mediated by arsenic - Zi-Yue Gao; Kun-Feng Qiu; Razvan Caracas; Bing-Cheng Luo; Xin Liu; Zheng-Yu Long; Deng-Yang He; Jia-Nan Fu; Mei-Jing Xu; Hao-Cheng Yu; Zheng-Jiang Ding; Jun Deng (Geochimica et Cosmochimica Acta, 2026)

Bioactive edestin peptides from hemp (Cannabis sativa L.) seeds improve exercise performance under hypobaric hypoxia - Rui Zhang; Jie Liu; Liang-Liang Chen; Jia-Qi Liu; Xiao-Qian Jin; Zi-Xian Fu; Jun-Bin Xiong; Bin Jia; Jun-Ling Shi; Da-Chuan Yin (Food Research International, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Mechanistic insights into the enhanced degradation of hydroxychloroquine by singlet oxygen in PMS and PMS/Cl2 systems: A comparative study - Zi-Han Feng; Zhen-Zhen Li; Dong-Su Bi; Fu-Xiang Tian; Ling-Yao Meng; Yan-Ting Jia; Yu-Qiong Gao; Xiao-Jun Hu (Journal of Environmental Management, 2026)

A rotating biomimetic graphene-microelectrode column for ultrafast electroporation-lysis and detection of pulmonary fungal pathogens - Quanying Fu; Keye Gong; Shaoqiong Feng; Xiaoqi Luo; Luteng Yang; Zi Ye; Jufeng Pan; Yuanyuan Feng; Jiasi Wang; Peisong Chen; Jianhua Zhou (Chemical Engineering Journal, 2026)

Reversible cross-linked epoxy adhesives based on dynamic covalent bonds - Yingpeng Zhou; Zi-Han Zhao; Jiajun Fu (Chemical Engineering Journal, 2026)

Mitochondrial ORF188 confers salt stress tolerance in rapeseed via an ATP-dependent enhancement of antioxidant capacity - Shi-Hang Fan; Zi-Hong Huang; Jun Li; Xiang Ji; Wei Hua; Zheng-Wei Fu (Plant Cell Reports, 2026)

Comprehensive analysis of Salvia uliginosa extract: HPLC-MS, GC-MS and evaluation of antioxidant and neuroprotective effects - Yang-xin Liao; Zi-fu Wang; Peng Zhao; Shi-mei Liao; Jia-wei Tang; Shi-jun Hu; Dong-hua Zhang; Xiao-hui Yan (Natural Product Research, 2026)

TMEM158-mediated TGF-β signaling pathway modulates the sensitivity of TP53-deficient osteosarcoma to USP14 inhibitors - Zi-Yu Chen; Miersalijiang Yasen; Song-Yao Jiang; Zi-Yi Ye; Qin-Xin Yang; Cui-Ni Lu; Yi Shi; Xin-Yun Liu; Ting-Ting Du; Xiao-Mei Tang; Da Fu; Yu-Shui Ma; et al. (Molecular and Cellular Biochemistry, 2026)

Monazite petrochronology and Nd isotopes deciphering dynamic magma sources in the genesis of the Himalayan leucogranites - Hui-Chan Huang; Peng Gao; Zhang-Jian Wu; Yan Wang; Zi-Fu Zhao; Changqing Yin (Lithos, 2026)

Evolution of tactoid structures and pore water distribution during wetting in saturated clay aggregates driven by montmorillonite-water interaction - Kai-wen Tong; Chang-fu Wei; Yong-gui Chen; Zi-yu Ding; Hao Wang; Ya-kun Tian; Rong Gui; Ling-ling Wu; Zhi-jun Zhang; Lin Hu (Computers and Geotechnics, 2026)

Harnessing Cuproptosis resistance to advance cancer therapeutics - Zi-Zhan Li; Tian-Fu Wu; Zhi-Jun Sun (Apoptosis, 2026)

Persteroid, a new steroid from the marine-derived fungus Penicillium sp. ZYX-Z-143 - Lu-Ting Dai; Li Yang; Zi-Peng Wang; Jiao-Cen Guo; Qing-Yun Ma; Qing-Yi Xie; Hao-Fu Dai; Zhi-Fang Yu; You-Xing Zhao (Natural Product Research, 2026)

Arching patterns in compacted clay: insights from plane-strain trapdoor tests - Xiang-Shen Fu; Han-Lin Wang; Zi-Jian Zhai; Ren-Peng Chen; Daniel Dias (Transportation Geotechnics, 2026)

Evolutionary mechanism of passive soil arching effect in sand at various relative densities and heights of fill - Han-Lin Wang; Zi-Jian Zhai; Xiang-Shen Fu; Xiao-Hu Zhang; Daniel Dias; Ren-Peng Chen (Transportation Geotechnics, 2026)

Paleoclimatic fluctuations as drivers of karst plant diversification in southern China - Ke Tan; Long-Fei Fu; Ming-Xun Ren; Xiao-Juan Li; Zi-Bing Xin; Ren-Fen Wang; Pramote Triboun; Truong Van Do; Fang Wen; Yi-Gang Wei (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Rice SINA E3 ligases dichotomously control ERECTA1 ubiquitination and stability to regulate panicle morphogenesis and grain yield - Zi-Qi Lu; Tao Guo; Ying-Jie Cao; Jun-Xiang Shan; Wang-Wei Ye; Nai-Qian Dong; Yi Kan; Yi-Bing Yang; Shuang-Qin Guo; Jie-Jie Lei; Xiao-Rui Mu; Ji-Fu Zhou; et al. (Molecular Plant, 2026)

Water quality management during nitrogen recovery from fish sludge in a novel dual-loop aquaponic system - Yongxia Zi; Tian Xia; Jiayi Zhao; Zhaowan Fu; Chew Tin Lee; Yueshu Gao; Chunjie Li (Journal of Water Process Engineering, 2026)

Nickel isotopic evidence for potential deep magmatic sulfide ore bodies in orogenic settings - Peng-Yi Li; Shui-Jiong Wang; Fu-Ping Pei; Guan-Wen Yu; Bing-Qian Ding; Zi-Cheng Guan; Kai Song; Wen-Liang Xu (Geochimica et Cosmochimica Acta, 2026)

TensorSymmetry: a package to get symmetry-adapted tensors disentangling spin-orbit coupling effect and establishing analytical relationship with magnetic order - Rui-Chun Xiao; Yuanjun Jin; Zhi-Fan Zhang; Zi-Hao Feng; Ding-Fu Shao; Mingliang Tian (Computer Physics Communications, 2026)

Anammox community characteristics and stable relationships centered on anammox bacteria - Yi-Cheng Wang; Hui-Min Fu; Hong-Yuan Liu; Han Wu; Zi-Han Zeng; Jian-Hong He; Meng-Jiao Gao; Peng Yan; Liang Zhang; You-Peng Chen (Chemical Engineering Journal, 2026)

Engineered hydrogels for siRNA delivery: From smart design to therapeutic impact - Shaohui Geng; Yijin Jiang; Huawei Wang; Anqi Liu; Xiuwen Wang; Ran Man; Jingyuan Fu; Yiwei Guan; Zi Ye; Zixuan Shu; Han Sheng; Jinian Wei; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “A carboxymethyl chitosan/trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration” [Carbohydrate Polymers 354 (2025) 123305] - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2026)

Interpretability-Enhanced Mineral Prospectivity Models: A Synergistic Approach Using Large Language Models, Knowledge Graphs, and Machine Learning - Zhen-Jie Zhang; Zi-Xing Yang; Fu-Yuan Jian; Si-Yuan Ban; Yi-Ming Wang (Mathematical Geosciences, 2026)

Effects of River Input on the Inorganic Nitrogen Components in Estuary–Bay Waters: Zhanjiang Bay, China - Fei Yue; Zi-Liang Chen; Ying-Ying Zeng; Guo-Huan Yang; Ji-Biao Zhang; Peng Zhang; Miao-Jian Fu (Journal of Marine Science and Engineering, 2025)
Rivers discharge a substantial amount of nutrients into the bay, which constitutes a key area of research in water pollution and environmental management. However, research on the influence of river input on various nitrogen components in semi-enclosed bays like the Zhanjiang Bay remains limited. This study conducted on-site monitoring and cultivation experiments in Zhanjiang Bay. Consequently, a systematic investigation was conducted on the influence of river inputs on the migration and change in different nitrogen components, primarily dissolved inorganic nitrogen (DIN). The results showed that the DIN flux during the rainy season was the greatest input flux, amounting to 9724 t, which accounted for 45.6% of the annual DIN flux. The fluxes of NO2-N and NO3-N were the highest during the rainy season, accounting for 49% and 52% of the total annual flux, respectively. Based on on-site cultivation under different salinity conditions (5, 15, and 25), the DIN content decreased much faster in lower-salinity waters, with the highest average daily change rate of −16.3 μmol/dm3 in a salinity of 5. This indicated that hydrodynamic mixing and exchange processes have a significant impact on the variations in inorganic nitrogen components. Therefore, the results of this study provide valuable insights into the migration and change in inorganic nitrogen components in estuarine water bodies. It also holds significance for guiding the treatment of environmental pollution in estuaries, such as addressing the sewage discharge from the steel industry.

Plantation forest stand age affects the characteristics and the chlorine reactivity of soil-derived dissolved organic matter - Xin-Yi Jiao; Su-Ping Liu; Shuang Peng; Zi-Hao Wu; Fu-Qiang Fan; Le Fang; Yan-Chao Jin; Peng Liu; Cai-Shan Wang; Ding Pan; Xue-Rong Wang; Ying-Zhi Ding; et al. (Water Research, 2025)

Investigation of microstructural characteristics and methane desorption in coal using surfactant treatment - Chen Ming-yi; Pei Zi-ting; Hu Shi-bo; Su Wei-wei; Tian Fu-chao; Zhang Xue-jie (Fuel, 2025)

Origin and genesis of post-collisional intrusive rocks in South Tibet and Himalaya: A review - Zhang-Jian Wu; Peng Gao; Yan Wang; Hui-Chan Huang; Zi-Fu Zhao; Yong-Fei Zheng (Earth-Science Reviews, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Comparison of various machine learning algorithms for landslide susceptibility assessment: A case study of Meishan township, Zhejiang Province, China - Du Bo Wang; Fu-Wang Zhong; Xuan-Wang Zi (Applied Geophysics, 2025)

Dexmedetomidine alleviates ferroptosis caused by traumatic brain injury via the NRF2/HO-1/GPX4 pathway - Jin-Jing Hao; Xue-lian Fang; Yi-Yang Chen; Zi-jun Meng; Fu-xing Dong; Xiao-fang Yang; Zheng Chu; Jin-xia Kuai; Haijun Bao (Metabolic Brain Disease, 2025)

Functional characterization of odorant binding proteins in Pharsalia antennata provides insights into diverse binding properties and the importance of C-terminal residues - Shu-Lin Li; Fu-Peng Li; Zi-Xuan Yang; Yu-Jie Zhao; Zhao-Qun Li; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Polybaric differentiation for arc magma genesis: a perspective from alumina saturation index - Peng Gao; Marcos García-Arias; William J. Collins; Long Chen; Hua Xiang; Hai-Ou Gu; Zi-Fu Zhao (Lithos, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Tight sandstone reservoirs in lacustrine environments: review and perspectives - Chen-Lin Hu; Zi-Qiang Lin; Xin Li; Jonathan Atuquaye Quaye; Zhi-Qiang Fu (International Geology Review, 2025)

Transcriptional control of male-specific pathway in temperature-dependent sex determination - Yin-Zi Ye; Jiameng Li; Weiming Li; Xiaonan Fu; Jiajun Zhang; Shilong Yang; Wei-Guo Du (Science Bulletin, 2025)

Biphasic continuously composite electrolyte design for high-performance solid-state Li–CO2 batteries - Qian-Cheng Zhu; Shu-Jian Li; Zi-Yuan Wang; Fu-Li Zhang; Jin-Hao Xie; De-Yu Mao (Chemical Engineering Journal, 2025)

Antinode-centre near-infrared tandem OLEDs enabled by ultrathin emissive layers - Min Song; Zheng Ren; Sheng-Fu Wang; Xiao-Bo Shi; Wei-Zhi Liu; Zi-Qi Feng; Dong-Ying Zhou; Pi-Tai Chou; Liang-Sheng Liao (Chemical Engineering Journal, 2025)

A fish-gelatin-modified multifunctional hydrogel with “salt-in-water” for dendrite-free flexible zinc-ion batteries - Wen-Long Cheng; Zi-Qiang Cheng; Zi-Zi Hu; Ming-Ming Hu; Guang-Xian Liu; Lin-Feng Yuan; Yan-Hui Fu; Xiao-Mei Sha; Zong-Cai Tu (Chemical Engineering Journal, 2025)

Singlet oxygen-driven non-radical oxidation of phenylurea herbicides in aqueous environment: Reaction behaviors and degradation mechanisms via unactivated PMS systems - Zi-Han Feng; Lin-Hao Xu; Fu-Xiang Tian; Fan Lai; Jing Ye; Yu-Qiong Gao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Pressure makes diamonds: Enhanced permeation resistance to petroleum hydrocarbons of a novel in-situ mixed wall material - Zhe-Yuan Jiang; Xian-Lei Fu; Yu-Ling Yang; Wei-Yi Xia; Min Wang; Heng Zhuang; Zi-Han Lu; Yan-Jun Du (Journal of Hazardous Materials, 2025)

Neurotoxicity of chronic nano-neodymium oxide exposure in zebrafish: Behavioral and molecular insights - Bao-Fu Zhang; Xing-Zhe Wu; Jin-Xia Wang; Yan-Ling Liao; Zi-Xin Cai; Yiyun Liu; De-Sheng Pei (Journal of Hazardous Materials, 2025)

Association of long-term PM2.5 and its components exposure with ovarian hyperstimulation syndrome risk in assisted reproductive technology patients - Jia-Liang He; Rui-Ling Liu; Yu-Ling Hu; Quan-Zi Yao; Zhi-Lei Xu; Li-Hong Geng; Tong Wang; Xin Luo; Ying-Ling Yao; Yong-Jia Zhang; Xue-Jiao Wang; Zhao-Hui Zhong; et al. (Environmental Pollution, 2025)

Real-time uncertainty quantification for KLT-based displacement estimation - Kang Zhou; Ming-Gang Duan; Ji-Yang Fu; Yun-Cheng He; Zi-Tong Li; Hai-Ou Shi; Jing Song (Engineering Structures, 2025)

Quorum-sensing Inhibitory Activity of Xanthones from Hypericum Curvisepalum N. Robson Against Chromobacterium Violaceum - Hong Zeng; Qiu-Ying He; Sheng-Qiang Yang; Xiao-Lian Wei; Jia-Zi Luo; Jing-Kai Zhou; Rong-Bing Fu; Li-Ping Teng; Zhong-Bo Zhou (Current Microbiology, 2025)

Antithrombotic macrocyclic sesquiterpene pyridine alkaloids from Tripterygium hypoglaucum - Qiong Jin; Jia-Shan Shen; Xian-Run Wu; Hui-Zhen Peng; Zi-Hao Fu; Li-Qiang Chen; Yun-Li Zhao; Min Ye; Xiao-Dong Luo (Phytochemistry, 2025)

Preparation, identification and potential mechanism of novel urate-lowering active peptide from hemp protein: From animal model to computer simulation - Meng-Qi Liu; Hong-Fu Zhao; Zi-Ying Zhao; Ying-Hua Zhang; Yan Dong (Food Research International, 2025)

Z-scheme MIL-88A(Fe)/LaFeO3 heterostructured photocatalyst: Boosting photo-Fenton activity for enhanced organic pollutant detoxification - Ruo-Xuan Mei; Peng Wang; Fu-Xue Wang; Zi-Chen Zhang; Xiao-Hong Yi; Zi-Yu Jia; Ke-Xin Li; Chong-Chen Wang (Environmental Research, 2025)

Molybdenum isotopes record slab inputs to the mantle source of late Triassic Arc Lavas, Northeast China - Zhigang Wang; Hui-Dong Zhang; Li-Qun Dai; Zi-Fu Zhao; Wei Fang (Chemical Geology, 2025)

Nutrient enrichment weakens the positive feedback of soil organic carbon decomposition to short-term warming in subtropical forests - Ming-Hui Meng; Chao Liang; Jin He; Zi-Yi Shi; Fu-Sheng Chen; Fang-Chao Wang; Xue-Li Jiang; Xiang-Min Fang (Plant and Soil, 2025)

Diffusion-driven zircon Zr isotopic fractionation during ultramafic–mafic magmatic differentiation - Li-Tao Ma; Li-Qun Dai; Shao-Bing Zhang; Ren-Xu Chen; Qiong-Xia Xia; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2025)

Precambrian history of the Altun microcontinent: review and synthesis - Yanguang Li; Guochao Sun; Zi-Fu Zhao; Mengqi Jin; Jianghua Zhao (International Geology Review, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

A biphasic nanoplatform with switchable biochemical programs for combined organelle-specific cancer therapy - Wanting Hao; Meng Zhang; Ruokun Li; Zi Fu; Xinyuan Cui; Zeyang Liu; Hongjing Jiang; Dalong Ni; Fuhua Yan (Chemical Engineering Journal, 2025)

Key role of recycled terrigenous sediments in generating continental arc magmatism in the West Qinling orogen, China - Li-Tao Ma; Li-Qun Dai; Hao Liang; Ye-Dan Hu; Qing-Cheng Yang; Zi-Fu Zhao; Guo-Chao Sun (Chemical Geology, 2025)

Sensor with Strong Solid Emission for Fluorescence Colormetric Detection of 1, 4-Dioxane in Water and Vapor Based on the Keto-Enol Isomerisation - Jing Wang; Zi-Ao Zong; Shi-Fu Huang; Mohd. Muddassir; Zhi-Yong Xing; Na-Na Li; Wen-Qiong Jiang (Journal of Fluorescence, 2025)

The role of ATG7-mediated ferroptosis in formaldehyde-induced ovarian injury in rats - Kun Mao; Hao-zhe Yan; Jia-qi Yang; Zi-xin Yin; Xin-qi Gao; Hao-fu Liu; Heng Su; Yuan-yuan Geng; Pan Ge; Dang-xia Zhou (Reproductive Toxicology, 2025)

An endophytic fungus Dichotomopilus funicola J-219 for the control of pigeon pea root rot caused by Rhizoctonia solani and its role in regulating the secondary metabolic defense response - Jie Gao; Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Zi-Yi Zhang; Xiao-Qing Wang; Yu-Jie Fu (Physiological and Molecular Plant Pathology, 2025)

Vibration reduction characteristics of steel-rubber periodic damper based on finite-domain quasi-surface wave effect - Yu-xuan Qin; Yang Tang; Zhe Zhao; Hai-chao Li; Fu-zhen Pang; Zi-teng Mao (Ocean Engineering, 2025)

Slowing wind increases soil carbon emissions in a fragmented subtropical forest: a study combining field and model experiments - Hao-Hao Wu; Ling-Ling Zhang; Ai-Min Liao; Hua-Wu Wu; Xiao-Ming Lai; Hai-Xia Zhang; Ye Xia; Yang Cao; Zi-Chun Zhu; Zhen-Ming Ji; Cong-Sheng Fu (Plant and Soil, 2025)

Adsorption characteristics of sulfate reducing bacteria Clostridium sp. on lignite surface - Huan He; Zi Yang Zhou; Di Zhan; Yong Zhang; Wen Cheng Xia; Bo Fu; Feng Juan Lan; Xiu Xiang Tao; Zai Xing Huang (Environmental Science and Pollution Research, 2025)

Exosomes secreted from M2-polarized macrophages inhibit osteoclast differentiation via CYLD - Zi-yan Guo; Nan-nan Yin; Xiao-fei Li; Meng-meng Wang; Xiao-na Sui; Cai-di Jiang; Ming-hua Xu; Xiao-e Jia; Chong-jian Fu; Tie-lou Chen; Xin Liu (Tissue and Cell, 2025)

Highly efficient and convenient QuEChERS using ZIF-67 derived magnetic nanoporous carbon for determination of carbamate pesticides in various vegetable and fruit samples - Zi-Ling Li; Xiao-Run Qi; Yi-Heng Xu; Jia-Qi Zhao; Gui-Fu Zuo; Man-Man Wang (Food Chemistry, 2025)

A carboxymethyl chitosan /trans-2-hexenal Schiff's base gel with controlled density using dynamic imine bonds: pH-controlled release and extended duration - Guang-shuo Zhou; Tao Zhang; Yan Jin; Guo-fu Zhang; Bo Kong; Da-yin Chen; Guo-xian Wang; Zi-shu Wang; Meng-ying Qi; Da-xia Zhang; Wei Mu; Nan Zou (Carbohydrate Polymers, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Quantitative analyses for wave energy evolution and dissipation processes under the gap resonance between two rectangular boxes - Xin-yu Wang; Yong Liu; Domenico D. Meringolo; Lin Lu; Fu Wang; Shao-dong Gong; Zi-bo Xia (Ocean Engineering, 2025)

Highly efficient Z-scheme CeO2/Bi2MoO6 heterojunction strengthened by redox mediator for photoelectrochemical detection of tetracycline with enhanced sensitivity - Li Li; Yanyu Xie; Chuanfa Luo; Guanwei Pen; Zi Min; Xigen Huang; Rumin Fu; Yansha Gao; Zongde Wang; Limin Lu (Food Chemistry, 2025)

Transient cooling performance and parametric characteristic of active–passive coupling cooling system integrated air-conditioner, PV-PCM envelope, and ice storage - Ying-Xi Huang; Zheng-Yu Shu; Zi-Quan Liu; Yang Cai; Wei-Wei Wang; Fu-Yun Zhao (Energy and Buildings, 2025)

Origin of the coeval Nb-enriched and arc mafic igneous rocks: Implications for Paleozoic tectonic evolution of the Southwestern Tianshan - Li-Tao Ma; Li-Qun Dai; Ye-Dan Hu; Zi-Fu Zhao (Chemical Geology, 2025)

Microbiome changes and characteristics under nutrient injection for enhanced oil production at Daqing oilfield - Zi-Yue Fu; Wen-Tao Chen; Gui-Na Qi; Zhao-wei Hou; Yi-Fan Liu; Li-Bin Shou; Lei Zhou; Shi-Zhong Yang; Xiao-Lin Wu; Ji-Dong Gu; Bo-Zhong Mu (International Biodeterioration & Biodegradation, 2025)

Impact of in–situ bioelectric field on biogas production, membrane fouling and microbial community in an anaerobic membrane bioreactor under sulfadiazine stress - Haojie Huang; Yutong Sun; Qing Du; Fu Gao; Zi Song; Zhiwen Wang; Suyun Chang; Xinbo Zhang; Wenshan Guo; Huu Hao Ngo (Chemical Engineering Journal, 2025)

Magnesium isotope constraints on the role of recycled carbonate-rich sediments in the formation of ultrapotassic magmatic rocks at a continental arc setting - Yu Chen; Yi-Xiang Chen; Fatma Gülmez; Ş. Can Genç; Guo-Chao Sun; Zi-Fu Zhao (Lithos, 2024)

AHR activation relieves deoxynivalenol-induced disruption of porcine intestinal epithelial barrier functions - Zi-Yan Hu; Shang-Jia Yang; Yuan-Hang Chang; Xue-Qi Wang; Rui-Qi Liu; Fu-Wei Jiang; Ming-Shan Chen; Jia-Xin Wang; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Yi Zhao; et al. (Journal of Hazardous Materials, 2024)

Lymph nodes in oral squamous cell carcinoma: a comprehensive anatomical perspective - Guang-Rui Wang; Nian-Nian Zhong; Lei-Ming Cao; Xuan-Hao Liu; Zi-Zhan Li; Yao Xiao; Kan Zhou; Yi-Fu Yu; Bing Liu; Lin-Lin Bu (Clinical & Experimental Metastasis, 2024)

Thalassospira aquimaris sp. nov. and Winogradskyella marincola sp. nov. two marine bacteria isolated from an agar-degrading co-culture - Zi-Yue Fu; Dao-Feng Zhang; Meng-Han Huang; Hong-Chuan Wang; Xiao-Ye Chen; Yu-Fang Yao; Yang Yuan; Wen-Jun Li (Antonie van Leeuwenhoek, 2024)

Evaluation and comparison of iohexol elimination by UV/peroxymonosulfate and UV/persulfate processes: Radical roles, influence factors and iodinated trihalomethanes formation - Chen-Cheng Mo; Fu-Xiang Tian; Bin Xu; Fan Lai; Yu-Qiong Gao; Yan Ma; Zi-Han Feng; Zi-Jian Yao; Dong-Su Bi; Xiao-Jun Hu (Journal of Water Process Engineering, 2024)

Revolutionizing nanozyme technology with metal-organic frameworks: Classification, catalytic mechanisms, regulation and applications in biotechnology - Yiran Wang; Yaqiong Yang; Jiachen Liu; Xiangyu Zi; Huayue Zhu; Xiaolong Sun; Yingjie Miao; Yongqian Fu (Chemical Engineering Journal, 2024)

Six element high-entropy Prussian blue analogue cathode enabling high cycle stability for sodium-ion batteries - Zhe Qian; Rui-Jie Luo; Cui Ma; Chong-Yu Du; Jie Zeng; Xuan Xu; Zhe Mei; Zi-Ting Zhou; Zheng-Wen Fu; Yong-Ning Zhou (Chemical Engineering Journal, 2024)

A novel temperature-responsive biphasic deep eutectic solvent-based solvent system: Integrated efficient extraction, enrichment and recovery of phytochemicals - Zi-Hui Cai; Xin-Yue Dong; Li-Tao Wang; Wan-Mei Zhou; Ya-Ning Wang; Jie Yang; Yu-Jie Fu (Chemical Engineering Journal, 2024)

Hohaiivirga grylli gen. nov., sp. nov., a New Member of the Family Methylobacteriaceae, Isolated from Cricket (Gryllus chinensis) - Hong-Chuan Wang; Meng-Han Huang; Dan-Yuan Guo; Wei He; Lu Wang; Zi-Yue Fu; Wen-Jun Li; Ai Hua Zhang; Dao-Feng Zhang (Current Microbiology, 2024)

Post-collisional reworking of juvenile mafic lower crust for the petrogenesis of late Triassic adakitic rocks in the East Kunlun Orogen - Gang Wen; Guo-Chao Sun; Zi-Fu Zhao; Li-Qun Dai; Yao Zhou (Lithos, 2024)

Genesis of high-Al chromitites from Xiaosuihe peridotite (Central Jilin Province, NE China): Implication for initial subduction of the Paleo-Asian ocean - Bing-Qian Ding; Fu-Ping Pei; Jing-Yang Wei; Jin-Rui Zhang; Zi-Cheng Guan; Kai Song; Tian-Jiao Sang; Peng-Yi Li (Lithos, 2024)

Enhanced production of health-promoting phenolic compounds using a novel endophytic fungus Talaromyces neorugulosus R-209 isolated from pigeon pea in a natural habitat by l-phenylalanine feeding - Jin-Xian Fu; Jiao Jiao; Qing-Yan Gai; Yu-Jie Fu; Jie Gao; Zi-Yi Zhang; Yuan Wang; Xiao-Qing Wang (World Journal of Microbiology and Biotechnology, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

A novel coupled bES-FEM formulation with SUPG stabilization for thermo-hydro-mechanical analysis in saturated porous media - Zi-Qi Tang; Xi-Wen Zhou; Yin-Fu Jin; Zhen-Yu Yin; Qi Zhang (Computers and Geotechnics, 2024)

Iodine/soluble starch cryogel: An iodine-based antiseptic with instant water-solubility, improved stability, and potent bactericidal activity - Wei Sun; Zi-Xi Wang; Yuxin Guo; Chengcheng Li; Ge Gao; Fu-Gen Wu (Carbohydrate Polymers, 2024)

Secular mantle wedge evolution due to variable slab fluid metasomatism: Evidence from Permian-Triassic mafic igneous rocks in the Paleo-Tethys tectonic regime - Ye-Dan Hu; Li-Qun Dai; Li-Tao Ma; Zi-Fu Zhao (Chemical Geology, 2024)

Sodic adakitic granites in the East Kunlun Orogen, China: Partial melting of ultrahigh-pressure metamorphic terranes during continental collision - Lei Qin; Guo-Chao Sun; Peng Gao; Zi-Fu Zhao; Li-Qun Dai; Gang Wen; You-Shan Xia; Yao Zhou (Chemical Geology, 2024)

Molybdenum isotopic evidence for the initiation of a big mantle wedge beneath eastern Asia - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Qi Chen; Jun Yan; Dayu Zhang; Ding-Sheng Jiang (Chemical Geology, 2024)

First identification of Mid-Miocene north–south trending dikes in the eastern Qiangtang terrane, eastern Tibet: Mantle melting and implications for plateau uplift - Chuan-Bing Xu; Jun Wang; Qiang Wang; Andrew C. Kerr; Wu-Fu Li; Jin-Heng Liu; Bing-Zhang Wang; Shan-Ping Li; Chun-Tao Wang; Zi-Long Wang; Lin Gong (Lithos, 2024)

A two-step method of cyclolinopeptide (linusorb) preparation from flaxseed cake via dry-screening - Zi-zhe Cai; Chen-xin Xu; Zi-liang Song; Jun-le Li; Ning Zhang; Jian-hao Zhao; Yee-Ying Lee; Martin J.T. Reaney; Fu-rong Huang; Yong Wang (Food Chemistry, 2024)

A degradable multi-functional packaging based on chitosan/silk fibroin via incorporating cellulose nanocrystals-stabilized cinnamon essential oil pickering emulsion - Jian-Dong Wang; Shi-Liang Yang; Guo-Sheng Liu; Quan Zhou; Li-Na Fu; Qi Gu; Zi-Hui Cai; Su Zhang; Yu-Jie Fu (Food Hydrocolloids, 2024)

Cross-linked g-C3N4 nanofibers enable thermal stable composite membranes for high-performance loose nanofiltration - Wan-Ting Lin; Ping Fu; Wan-Long Li; Yuan-Hui Yu; Zi-Lu Zhang; Hong-Yu Fan; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Chemical Engineering Journal, 2024)

Parotid Gland Segmentation Using Purely Transformer-Based U-Shaped Network and Multimodal MRI - Zi’an Xu; Yin Dai; Fayu Liu; Siqi Li; Sheng Liu; Lifu Shi; Jun Fu (Annals of Biomedical Engineering, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

In-situ trace element and Sr isotope in mantle xenoliths from the West Qinling orogen: Evidence for carbonate metasomatism - Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun (Lithos, 2024)

Eocene rhyolites in the Shanglaxiu-Xialaxiu area of north-eastern Qiangtang Block, Tibet: Partial melting of juvenile crust? - Yi-Wen Wei; Jun Wang; Qiang Wang; Bing-Zhang Wang; Andrew C. Kerr; Wu-Fu Li; Shan-Ping Li; Jin-Heng Liu; Chun-Tao Wang; Zi-Long Wang (Lithos, 2024)

Pollution characteristics, source apportionment and absorption spectra of size-resolved PAHs in atmospheric particles in a cold megacity of China - De-Qi Wang; Shi-Ming Jia; Li-Yan Liu; Zi-Feng Zhang; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

A NIR-II quantum dot-assisted dual-color imaging strategy enables simultaneous tracking of two subtypes of extracellular vesicles in vivo - Xing-Chi Liu; He-Jing Zhang; Rui Xu; Jing Liu; Hou-Fu Xia; Qi-Hui Xie; Zhi-Quan Tian; Zi-Li Yu; Gang Chen (Chemical Engineering Journal, 2024)

GHK-Cu/Pionin-loaded in situ electrospun PVB/PVP smart dressing promotes wound healing via anti-oxidant, anti-inflammatory, antimicrobial, and tissue regenerative effects - Yan Wang; Zhichao Zheng; Janak L. Pathak; Haoyu Cheng; Sizhen Huang; Zi Fu; Ping Li; Lihong Wu; Huade Zheng (Chemical Engineering Journal, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Ocean eddy detection based on YOLO deep learning algorithm by synthetic aperture radar data - Nannan Zi; Xiao-Ming Li; Martin Gade; Han Fu; Sisi Min (Remote Sensing of Environment, 2024)

Syn- and post-collisional mafic igneous rocks from the East Kunlun Orogenic Belt: Implications for recycling of subducting continental crust during the Silurian-Devonian - Li-Tao Ma; Guo-Chao Sun; Li-Qun Dai; Zi-Fu Zhao; Ye-Dan Hu; Qing-Cheng Yang; Lei Qin; Bing Gong (Lithos, 2024)

Pickering extremulsion rich in lipophilic phytochemicals: Preparation, characterization and application - Xu Han; Cong-Jia Duan; Zi-Fei Wei; Jian Xu; Cheng-Dong Nie; Yuan-Hang Chang; Bo-wen Zhai; Yu-Jie Fu (Journal of Food Engineering, 2024)

Mo-Mg isotopes trace the role of serpentinite in generating arc magmatism - Qing-Chen Yang; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Guo-Chao Sun; Bing Gong (Chemical Geology, 2024)

Tanshinone IIA is superior to paricalcitol in ameliorating tubulointerstitial fibrosis through regulation of VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy - Jing-Yi Zeng; Yu Wang; Fu-Yuan Hong; Miao Miao; Yu-Ying Jiang; Zi-Xuan Qiao; Yun-Tao Wang; Xiao-Rong Bao (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)
Glomerulosclerosis and tubulointerstitial fibrosis (TIF) are closely involved in the development of diabetic nephropathy (DN). Moreover, the development of TIF is closely related to epithelial-to-mesenchymal transition (EMT). Tanshinone IIA (Tan) has various pharmacological effects, especially the anti-fibrotic effect. And it is mainly used in the clinical treatment of cardiovascular diseases. Currently, the protective effect of Tan on DN and its possible mechanism have not been clearly elucidated. Our previous studies illustrated that Tan could improve the EMT of HK-2 cells induced by high glucose by regulating the vitamin D receptor (VDR)/Wnt/β-catenin pathway. Here, we collected demographic information and laboratory results from the National Health and Nutrition Examination Survey (NHANES) database in order to investigate the relationship between VD and DN. Then, we established a DN model and treated DN rats with Tan and paricalcitol (Par) for 6 weeks. We subsequently compared the changes in general condition, renal function, pathological changes, and TIF-related protein expression levels of control rats, DN rats induced by STZ, DN rats with Tan at 5.4 mg/kg, DN rats with Tan at 10.8 mg/kg, and DN rats with Par at 0.054 µg/kg, to explore the effect and mechanism of Tan and Par on DN rats. The results showed that VD had a protective effect against DN in diabetic patients. And we found that Tan had a protective effect on renal fibrosis in DN rats, which was superior to Par in improving the symptoms of “three more and one less,” reducing fasting blood glucose level, improving renal index, BUN/SCr, and UACR, reducing histopathological damage of kidney, and improving the expression of fibrosis-related proteins in kidney tissue by regulating VDR/Wnt/β-catenin pathway. Tan was superior to Par in ameliorating tubulointerstitial fibrosis by regulating VDR/Wnt/β-catenin pathway in rats with diabetic nephropathy.

Were oxygen isotopes of hydrothermally altered minerals just elevated by the 18O-enriched water? Theoretical inversion with thermodynamics and kinetics - Chun-Sheng Wei; Zi-Fu Zhao (Mineralogy and Petrology, 2024)

Alkaloids from the stems of Fissistigma maclurei Merr. inhibit the proliferation of synoviocytes - Mu-Tao Liang; Xiao-Zheng Zhang; Zi-Hao Chen; Chuan-Shan Fu; Duo-Jiang Li; Guo-Ze Chen; Ji-Ling Yi; Xue-Ming Zhou (Natural Product Research, 2024)

New insights into functional divergence and adaptive evolution of uncultured bacteria in anammox community by complete genome-centric analysis - Yi-Cheng Wang; Yanping Mao; Hui-Min Fu; Jin Wang; Xun Weng; Zi-Hao Liu; Xiao-Wei Xu; Peng Yan; Fang Fang; Jin-Song Guo; Yu Shen; You-Peng Chen (Science of The Total Environment, 2024)

Prussian blue analogue nanospheres immobilized on self-floating biochar for micropollutant degradation via photo-Fenton process - Fu-Xue Wang; Zi-Wei Zhang; Zi-Chen Zhang; Ke-Xin Li; Ya Li; Hong-Yu Chu; Chong-Chen Wang; Jian-Feng Wang; Long Chen; Wen Liu; Hailong Wang; Peng Wang (Chemical Engineering Journal, 2024)

Fluid-metasomatized rocks with extremely low δ26Mg values in subducted oceanic lithosphere: Implications for mantle Mg isotope heterogeneity and the origin of low-δ26Mg magmas - Jia-Wei Xiong; Yi-Xiang Chen; Marco Scambelluri; Xin-Yue Qiao; Yu Chen; Fang Huang; Donato Belmonte; Zi-Fu Zhao (Geochimica et Cosmochimica Acta, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Titanite geochemistry traces extreme differentiation of granitic magma in the collisional orogen - Kun Zhou; He-Zhi Ma; Yi-Xiang Chen; Fang-Yue Wang; Zi-Fu Zhao (Lithos, 2024)

Subducted serpentinite contributes to the formation of arc lavas with heavy Mo isotopic compositions - Fu-Qiang Dai; Yi-Xiang Chen; Ren-Xu Chen; Zi-Fu Zhao; Jie Li; Yu Wang (Geochimica et Cosmochimica Acta, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

High-density bin-based genetic map reveals a 530-kb chromosome segment derived from wild peanut contributing to late leaf spot resistance - Jiaowen Pan; Xiaojie Li; Chun Fu; Jianxin Bian; Zhenyu Wang; Conghui Yu; Xiaoqin Liu; Guanghao Wang; Ruizheng Tian; Xiaofeng Song; Changsheng Li; Han Xia; et al. (Theoretical and Applied Genetics, 2024)

Genetic architecture of ecological divergence between Oryza rufipogon and Oryza nivara - Qing‐Lin Meng; Cheng‐Gen Qiang; Ji‐Long Li; Mu‐Fan Geng; Ning‐Ning Ren; Zhe Cai; Mei‐Xia Wang; Zi‐Hui Jiao; Fu‐Min Zhang; Xian‐Jun Song; Song Ge (Molecular Ecology, 2024)
Ecological divergence due to habitat difference plays a prominent role in the formation of new species, but the genetic architecture during ecological speciation and the mechanism underlying phenotypic divergence remain less understood. Two wild ancestors of rice ( Oryza rufipogon and Oryza nivara ) are a progenitor‐derivative species pair with ecological divergence and provide a unique system for studying ecological adaptation/speciation. Here, we constructed a high‐resolution linkage map and conducted a quantitative trait locus (QTL) analysis of 19 phenotypic traits using an F 2 population generated from a cross between the two Oryza species. We identified 113 QTLs associated with interspecific divergence of 16 quantitative traits, with effect sizes ranging from 1.61% to 34.1% in terms of the percentage of variation explained (PVE). The distribution of effect sizes of QTLs followed a negative exponential, suggesting that a few genes of large effect and many genes of small effect were responsible for the phenotypic divergence. We observed 18 clusters of QTLs (QTL hotspots) on 11 chromosomes, significantly more than that expected by chance, demonstrating the importance of coinheritance of loci/genes in ecological adaptation/speciation. Analysis of effect direction and v ‐test statistics revealed that interspecific differentiation of most traits was driven by divergent natural selection, supporting the argument that ecological adaptation/speciation would proceed rapidly under coordinated selection on multiple traits. Our findings provide new insights into the understanding of genetic architecture of ecological adaptation and speciation in plants and help effective manipulation of specific genes or gene cluster in rice breeding.

Kelp breeding in China: Challenges and opportunities for solutions - Zi‐Min Hu; Ti‐Feng Shan; Quan‐Sheng Zhang; Fu‐Li Liu; Alexander Jueterbock; Gaoge Wang; Zhong‐Min Sun; Xiang‐Yu Wang; Wei‐Zhou Chen; Alan T. Critchley; Nai‐Hao Ye (Reviews in Aquaculture, 2024)
Breeding has played an important role in the mariculture and industrialization of kelp in China. However, the current kelp breeding systems in China have encountered some problems relating to germplasm diversity, management, technological innovations, and regional co‐operation. This review summarizes the main challenges, such as top‐down and fragmented management of germplasm libraries, as well as private industry breeding without government regulations, inter‐cultivar accidental admixing and genetic erosion, loss of heterozygosity due to repeated selection and self‐crossing. We outline multiple potential approaches to breed cultivars with improved qualitative/quantitative traits which can be subjected to changing environments, for example: (i) establishing a national germplasm repository to enhance integrative collection and preservation of kelp resources; (ii) planning and implementing kelp breeding programmes according to strategic priorities and goal‐orientations; (iii) optimizing a hybridization‐based breeding pipeline to produce robust cultivars through the introgression of novel alleles and thus the expression of hybrid vigour; (iv) enriching the high‐quality annotated reference genomes and functional analysis of trait‐associated markers/loci to develop DNA‐based breeding technologies; (v) developing new priming‐based (e.g., thermal and disease resistance) bio‐engineering breeding strategies to meet future unpredictable climate change; and (vi) breeding towards an ecological kelp‐microbiome interaction‐based technique to produce cultivars with enhanced performance and adaptability to environmental scenarios. Collectively, the lessons learned from kelp breeding in China and the solutions proposed here may not only potentially improve or re‐invigorate the Chinese kelp industry, but will also assist other developing countries in taking corrective actions to develop a sustainable future kelp farming industry.

The level of CmFRQ is associated with the degeneration and rejuvenation of Cordyceps militaris fruiting body - Ming-Jia Fu; Dan-Dan Zhang; Jing-Mei Peng; Lei Feng; Zi-Hai Yang; Zi-Yan Huang (Biologia, 2024)

Occurrence, seasonal variation and gas/particle partitioning of current used pesticides (CUPs) across 60 °C temperature and 30° latitudes in China - Liang Wang; Gang Cao; Zi-Feng Zhang; Li-Yan Liu; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Journal of Hazardous Materials, 2024)

Centrifuge investigation on behavior of geosynthetic-encased stone column supported embankment under freeze-thaw cycles - Zi-Ang Gu; Fu-Jun Niu; Jian-Feng Chen; Chungsik Yoo (Geotextiles and Geomembranes, 2024)

Adsorption enhances CH4 transport-driven hydrate formation in size-varied ZIF-8: Micro-mechanism for CH4 storage by adsorption-hydration hybrid technology - Shujun Chen; Jun Duan; Xianfeng Xie; Yue Fu; Mucong Zi (Chemical Engineering Journal, 2024)

Synthesis and cytotoxic activity of ethyl ferulate derivatives as potent anti-inflammatory agents - Dan-ni Fu; Zi-yi Kong; Wen Sun; Chun-mei Bai; Yun Wu; Ming Bian; Qian-qian Ma (Natural Product Research, 2024)

Self-assembled Fe3O4-NH2 @g-C3N4 composite for magnetic solid-phase extraction of benzophenones in sea water and lake water coupled with LC-MS/MS determination - Man-Man Wang; Zi-Ling Li; Han Wu; Ke-Yan Chen; Fan Guo; Gui-Fu Zuo; Yu He; Xue-Bo Yin (Journal of Hazardous Materials, 2024)

Ambient ozone and ovarian reserve in Chinese women of reproductive age: Identifying susceptible exposure windows - Shuangyan Liu; Lin Liu; Xin Ye; Mingjian Fu; Wei Wang; Yunhua Zi; Xinliu Zeng; Kuai Yu (Journal of Hazardous Materials, 2024)

A metal-phenolic network-assembled nanotrigger evokes lethal ferroptosis via self-supply loop-based cytotoxic reactions - Xinping Zhang; Yuxin Guo; Xiaoyang Liu; Shun-Yu Wu; Ya-Xuan Zhu; Shao-Zhe Wang; Qiu-Yi Duan; Ke-Fei Xu; Zi-Heng Li; Xiao-Yu Zhu; Guang-Yu Pan; Fu-Gen Wu (Chemical Engineering Journal, 2024)

Vector-mediated viral exchange between crops and weedy plants - Xiao-bin Shi; Zhuo Zhang; Fan Li; Evan L. Preisser; Li-ping Huang; De-yong Zhang; Zhan-hong Zhang; Song-bai Zhang; Xu-guo Zhou; An-sheng Zhang; Hui Liu; Yuan-hua Wu; et al. (Journal of Pest Science, 2024)

Cross-regional scale studies of organochlorine pesticides in air in China: Pollution characteristic, seasonal variation, and gas/particle partitioning - Liang Wang; Gang Cao; Li-Yan Liu; Zi-Feng Zhang; Shi-Ming Jia; Meng-Qi Fu; Wan-Li Ma (Science of The Total Environment, 2023)

Phenanthrene release-migration characteristics and potential influencing mechanisms from paddy soil to overlying water under bioturbation in a rice-fish coculture agroecosystem - Nan Sun; Jin Liu; Zi-Jian Wang; Shuang Liu; Hao Cheng Wang; Qiang Fu (Journal of Cleaner Production, 2023)

Bioprocessing of pigeon pea roots by a novel endophytic fungus Penicillium rubens for the improvement of genistein yield using semi-solid-state fermentation with water - Xiao-Jia He; Jiao Jiao; Qing-Yan Gai; Jin-Xian Fu; Yu-Jie Fu; Zi-Yi Zhang; Jie Gao (Innovative Food Science & Emerging Technologies, 2023)

Molybdenum isotopic heterogeneity for intraplate basalts and its origin - Wei Fang; Li-Qun Dai; Zi-Fu Zhao (Chemical Geology, 2023)

Mo isotopes record recycling of anoxic sediment in a Paleo-oceanic subduction zone - Xiang Fu; Wei Fang; Li-Qun Dai; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

CDKN2B-AS1 mediates proliferation and migration of vascular smooth muscle cells induced by insulin - Hao-jie Jin; Zi-heng Wu; Bao-fu Zhang; Jie Deng; Yin-dong Xu; Xin-yu Wang; Zheng-yang Song; Xin-wu Lu; Wan-tie Wang; Xiang-tao Zheng (Cell and Tissue Research, 2023)

Numerical simulation of flow instability induced by a fixed cylinder placed near a plane wall in oscillating flow - Zi-Fang Li; Jiang-Hua Li; Jian-Zhao Wu; Kai-Leong Chong; Bo-Fu Wang; Quan Zhou; Yu-Lu Liu (Ocean Engineering, 2023)

High internal phase Pickering emulsions stabilized by modified sturgeon myofibrillar protein for quercetin delivery - Shi-ke Shen; Yue-wen Chen; Wen-tao Yu; Qian-yun Bu; Jing-jing Fu; Zi-yi Pan; Yi-tong Wang (Food Hydrocolloids, 2023)

Trace elements and Li isotopes distinguish between liquid and solid phases contributing to mafic arc magmas - Li-Tao Ma; Li-Qun Dai; Yong-Fei Zheng; Zi-Fu Zhao; Bing Gong; Yilin Xiao; Fengtai Tong (Lithos, 2023)

Advanced electrooxidation of florfenicol using 3D printed Nb2O5/Ti electrodes: Degradation efficiency, dehalogenation performance, and toxicity reduction - Yun-fei Zhang; Jia-le Gao; Shen-gui Chen; Lei Li; Jian-hui Xu; Dan Li; Yu-feng Liu; Xin Quan; Xin Fu; Ya-zi Xie; Jing-nan Wu; Dan-ying Lin; et al. (Chemical Engineering Journal, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Magnesium–oxygen isotope constraints on the origin of rodingites in oceanic lithosphere - Mei-Shan Zhao; Yi-Xiang Chen; Jia-Wei Xiong; Xin-Yue Qiao; Yong-Fei Zheng; Wen-Yong Duan; Fang Huang; Zi-Fu Zhao (Chemical Geology, 2023)

Melatonin alleviates cisplatin-induced mice spermatogenesis defects - Zhu Peng; Wang Zhi Xin; Zhang Yu Sheng; Teng Zi; Liu Ya Nan; Wang Ze Lin; Liu Fu Jun; Liu Xue Xia (Reproductive Toxicology, 2023)

Design, synthesis and biological activity of novel triketone herbicides containing natural product fragments - Zi-Bin Jiang; Shuang Gao; Wei Hu; Bo-Ren Sheng; Juan Shi; Fei Ye; Ying Fu (Pesticide Biochemistry and Physiology, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Effect of humic acid-modified attapulgite on polycyclic aromatic hydrocarbon adsorption and release from paddy soil into the overlying water in a rice-crab coculture paddy ecosystem and the underlying process - Nan Sun; Jin Liu; Bo-Wei Qi; Li-Li Lu; Hui-Ling Du; Shuang Li; Chang-Qing Li; Si-Wen Jiang; Zi-Jian Wang; An-Pei Yang; Guang-Lei Zhu; Tian-Yi Wang; et al. (Chemosphere, 2023)

Identify nitrogen transport paths and sources contribution in karst valley depression area using isotopic approach - Meng Lu; Fu-Jun Yue; Xiao-Dan Wang; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Journal of Environmental Management, 2023)

Barium isotope behavior during interaction between serpentinite-derived fluids and metamorphic rocks in the continental subduction zone - Anxia Chen; Yi-Xiang Chen; Xiaofeng Gu; Zhen Zeng; Zicong Xiao; Hans-Peter Schertl; Xiqiu Han; Zi-Fu Zhao; Fang Huang (Geochimica et Cosmochimica Acta, 2023)

Can the mix-charged NF membrane directly obtained by the interfacial polymerization of PIP and TMC? - Qiu-Yu Zhu; Zi-Yun Xu; Jie-Han Fu; Jie Huang; Zhen-Liang Xu; Min Tong; En-Chao Li; Yong-Jian Tang (Desalination, 2023)

Modulating the interfacial built-in electric field in oxygen vacancies-enriched Ru/MxOy@C (M = V, Nb, Ta) ordered macroporous heterojunctions for electrocatalytic hydrogen production - Xiao Hui Chen; Hong Chuan Fu; Xiao Lin Li; Ting Li; Qing Zhang; Zi Qing Li; Yuan Hao Luo; Jing Lei Lei; Nian Bing Li; Hong Qun Luo (Chemical Engineering Journal, 2023)

Influence on the levels of PAHs and methylated PAHs in surface soil from pollution control in China: Evidence in 2019 data compared with 2005 and 2012 data - Fu-Jie Zhu; Zi-Feng Zhang; Li-Yan Liu; Hong Yao; Hong-Liang Jia; Zhi Zhang; Song Cui; Bo Meng; Gang Cao; Peng-Hao Su; Xiao-Xuan Mao; Bao-Long Li; et al. (Science of The Total Environment, 2023)

Magmatism and thermal effect of the Late Paleoproterozoic layered complex in the Jining terrane, North China Craton: Evidence from magmatic cooling duration and crust-mantle interaction - Wei-Peng Zhu; Wei Tian; Bin Wang; Ming-Yue Gong; Bin Fu; Zi-Long Wang; Chun-Jing Wei (Precambrian Research, 2023)

Two generations of crustal anatexis in association with two-stage exhumation of ultrahigh-pressure metamorphic rocks in the Dabie orogen - Qiong-Xia Xia; Meng Yu; Er-Lin Zhu; Ren-Xu Chen; Wan-Cai Li; Yong-Fei Zheng; Zi-Fu Zhao; Zhao-Ya Li (Lithos, 2023)

Mechanistic insights into the migration behavior of cadmium (Cd) in the soil and groundwater systems at a construction site: Experimental and numerical analysis - Da–Mao Xu; Ze–Lin Xu; Zi–Qi Mu; Bai–Hong An; Xiao–Wen Fang; Rong–Bing Fu (Journal of Environmental Chemical Engineering, 2023)

Development of an Antarctic krill oil based self-microemulsion drug delivery system and its enhancement of bioaccessibility for curcumin - Dong-wen Fu; Ye Tian; Zi-han Wang; Jin-zhe Li; Da-yong Zhou; Bei-wei Zhu; Liang Song (Food Bioscience, 2023)

Molybdenum isotopes record recycling of subducting sediment in active continental margin, Northeast China - Wei Fang; Li-Qun Dai; Xiang Fu; Zi-Fu Zhao; Bing Gong; Yong-Fei Zheng (Chemical Geology, 2023)

CP3d: A comprehensive Euler-Lagrange solver for direct numerical simulation of particle-laden flows - Zheng Gong; Zi Wu; Chenge An; Bangwen Zhang; Xudong Fu (Computer Physics Communications, 2023)

Temporal geochemical variation in early Paleozoic mafic rocks from the Qinling orogen: Implications for the evolution of slab fluids during oceanic subduction - Hai-Yang Yan; Guo-Chao Sun; Zi-Fu Zhao; Li-Qun Dai; Fei Zheng (Chemical Geology, 2023)

Metatranscriptomic insights into the microbial electrosynthesis of acetate by Fe2+/Ni2+ addition - Jie Zhang; He Liu; Yan Zhang; Bo Fu; Chao Zhang; Min-Hua Cui; Ping Wu; Zi-Wei Guan (World Journal of Microbiology and Biotechnology, 2023)

Age and composition of Neoproterozoic diabase dykes in North Altyn Tagh, northwest China: implications for Rodinia break-up - Yanguang Li; Shuguang Song; Xiaoyong Yang; Zi-Fu Zhao; Jinlong Dong; Xiaofeng Gao; Michael T.D. Wingate; Chao Wang; Meng Li; Mengqi Jin (International Geology Review, 2023)

TMT-based quantitative proteomics analysis reveals the differential proteins between fresh and frozen-thawed sperm of yak (Bos grunniens) - Yilin Fan; Xiaowei Li; Yu Guo; Xiaoqiang He; Yanwen Wang; Dan Zhao; Yan Ma; Xinxin Feng; Jiyue Zhang; Jian Li; Xiangdong Zi; Xianrong Xiong; et al. (Theriogenology, 2023)

Molecular insights into CH4/H2O transport and hydrate formation in hydrophobic metal-organic frameworks ZIF-8: Implication for CH4 storage by adsorption-hydration hybrid method - Jun Duan; Xinyu Jiang; Yue Fu; Shujun Chen; Mucong Zi (Fuel, 2023)

Tailoring the whole-cell sensing spectrum with cyborgian redox machinery - Kai Yang; Zi-Jie Lu; Tian-Yu Zhu; Jing-Xian Wang; Fu-Qiao Yang; Syed Zaghum Abbas; Jun Zhou; Zhugen Yang; Jian-Li Mi; Sai Kishore Ravi; Yang-Chun Yong (Analytica Chimica Acta, 2023)

Petrogenesis of the Chakabeishan pegmatites, North Qaidam Terrane: Implications for Indosinian lithium mineralization in the northern Tibetan Plateau - Jin-Heng Liu; Qiang Wang; Bing-Zhang Wang; Wu-Fu Li; Chuan-Bing Xu; Shan-Ping Li; Zi-Long Wang; Lu-Lu Hao; Tai-Zhong Song; Chun-Tao Wang; Ying Zheng; Jin-Shou Wang (Lithos, 2023)

Application of a novel and green temperature-responsive deep eutectic solvent system to simultaneously extract and separate different polar active phytochemicals from Schisandra chinensis (Turcz.) Baill - Xin-Yu Yan; Zi-Hui Cai; Peng-Quan Zhao; Jian-Dong Wang; Li-Na Fu; Qi Gu; Yu-Jie Fu (Food Research International, 2023)

Selective oxidation of aqueous organic pollutants over MOFs-based catalysts: A mini review - Fu-Xue Wang; Zi-Chen Zhang; Chong-Chen Wang (Chemical Engineering Journal, 2023)

Distinct contribution of aqueous solutions and hydrous melts to the mantle sources: Geochemical evidence from Late Paleozoic igneous rocks in Southwestern Tianshan, Western China - Li-Tao Ma; Li-Qun Dai; Zi-Fu Zhao; Fang Huang; Bing Gong (Lithos, 2023)

National-scale monitoring of historic used organochlorine pesticides (OCPs) and current used pesticides (CUPs) in Chinese surface soil: Old topic and new story - Liang Wang; Zi-Feng Zhang; Li-Yan Liu; Fu-Jie Zhu; Wan-Li Ma (Journal of Hazardous Materials, 2023)

A green and designable natural deep eutectic solvent-based supramolecular solvents system: Efficient extraction and enrichment for phytochemicals - Zi-Hui Cai; Jian-Dong Wang; Lin Liu; Liu-Ding Ruan; Qi Gu; Xin-Yu Yan; Li-Na Fu; Peng-Quan Zhao; Su Zhang; Yu-Jie Fu (Chemical Engineering Journal, 2023)

Paracoccus marinaquae sp. nov., isolated from coastal water of the Yellow Sea - Hua-Peng Xue; Zi-Yue Fu; Wei He; Lei Wang; Wen-Jun Li; Ai Hua Zhang; Jian-Ke Huang; Dao-Feng Zhang; Zhe Zhao (Archives of Microbiology, 2023)

Strengthen the purification of eutrophic water and improve the characteristics of sediment by functional ecological floating bed suspended calcium peroxide and sponge iron jointly - Zheng Zhu; Yi Wang; Xue-Yi Han; Wen-Huai Wang; Hao-Min Li; Zi-Qi Yue; Wei Chen; Fu-Rong Xue (Journal of Environmental Management, 2023)

The effect of reservoir expansion from underground karst cave to surface reservoir on water quality in southwestern China - Meng Lu; Xiao-Dan Wang; Fu-Jun Yue; Zi-Han Liu; Zhi-Yu Shi; Ping Zhang (Environmental Science and Pollution Research, 2022)

Ginsenoside Rb1 inhibits oxidative stress-induced ovarian granulosa cell injury through Akt-FoxO1 interaction - Ping Zhou; Feng Deng; Zi Yang; Canhui Cao; Hongcui Zhao; Fenting Liu; Ke Zhong; Lin Fu; Tianliu Peng; Di Sun; Hui Liu; Rong Li; et al. (Science China Life Sciences, 2022)

The heterogeneous orogenic lithospheric mantle: whole rock and mineral geochemical evidence from early Paleozoic mafic intrusives in the Qilian orogen, China - Qi Chen; Li-Qun Dai; Zi-Fu Zhao; Yong-Fei Zheng; Yao Zhou (Contributions to Mineralogy and Petrology, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

Correction to: Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Brevibacillus dissolubilis sp. nov., Isolated from Fresh Water - Wei Li; Zhao-Xuan Wang; Fu Ma; Zhi-Da Zi; Han-Yi Chen; De Zhou; Jie Lv (Current Microbiology, 2022)

Differential ubiquitome analysis of Cordyceps militaris lysine-ubiquitinated proteins affected by blue light - Zi-Yan Huang; Lei Feng; Ming-Jia Fu; Dan-Dan Zhang (Biologia, 2022)

Microvirga puerhi sp. nov., isolated from Puerh tea garden soil - Zhi-Da Zi; Wen Wen; Fu Ma; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2022)

Improved and Flexible HDR Editing by Targeting Introns in iPSCs - Juan Fu; Ya-Wen Fu; Juan-Juan Zhao; Zhi-Xue Yang; Si-Ang Li; Guo-Hua Li; Zi-Jun Quan; Feng Zhang; Jian-Ping Zhang; Xiao-Bing Zhang; Chang-Kai Sun (Stem Cell Reviews and Reports, 2022)
Highly efficient gene knockout (KO) editing of CRISPR–Cas9 has been achieved in iPSCs, whereas homology-directed repair (HDR)-mediated precise gene knock-in (KI) and high-level expression are still bottlenecks for the clinical applications of iPSCs. Here, we developed a novel editing strategy that targets introns. By targeting the intron before the stop codon, this approach tolerates reading frameshift mutations caused by nonhomologous end-joining (NHEJ)-mediated indels, thereby maintaining gene integrity without damaging the non-HDR-edited allele. Furthermore, to increase the flexibility and screen for the best intron-targeting sgRNA, we designed an HDR donor with an artificial intron in place of the endogenous intron. The presence of artificial introns, particularly an intron that carries an enhancer element, significantly increased the reporter expression levels in iPSCs compared to the intron-deleted control. In addition, a combination of the small molecules M3814 and trichostatin A (TSA) significantly improves HDR efficiency by inhibiting NHEJ. These results should find applications in gene therapy and basic research, such as creating reporter cell lines.

Four types of acoustic emission characteristics during granular stick-slip evolution - Zi-ming Liu; Yao Jiang; Dao-jie Wang; Yan-ju Fu (Journal of Mountain Science, 2022)

A concise review of the brown seaweed Sargassum thunbergii — a knowledge base to inform large-scale cultivation efforts - Fu-Li Liu; Jing-Jing Li; Zhou-Rui Liang; Quan-Sheng Zhang; Feng-Juan Zhao; Alexander Jueterbock; Alan T. Critchley; Stephen L. Morrell; Jorge Assis; Yong-Zheng Tang; Zi-Min Hu (Journal of Applied Phycology, 2021)

A semi-idealized modeling study on the long-lived eastward propagating mesoscale convective system over the Tibetan Plateau - Shenming Fu; Zi Mai; Jianhua Sun; Wanli Li; Qi Zhong; Jiaren Sun; Yuanchun Zhang (Science China Earth Sciences, 2021)

Assessing the environmental impact of China’s tourism activities: a tourism heat footprint method - Shuxin Wang; Weihong Cao; Jiankuo Du; Pingping Tang; Hengyang Fu; Zi Tang; Jiamei Li (Environmental Science and Pollution Research, 2021)

Impact of rhizosphere microorganisms on arsenic (As) transformation and accumulation in a traditional Chinese medical plant - Jiao-Jiao Li; Long Yang; Cui-Ping Miao; Ya-Jun Teng; Zi-Hao Fu; Chang-Lei Cheng; Xue-Xiu Chang; Yu Qian; Li-Xing Zhao (Environmental Science and Pollution Research, 2021)

Landslide mapping and analysis along the China-Pakistan Karakoram Highway based on SBAS-InSAR detection in 2017 - Xiao-jun Su; Yi Zhang; Xing-min Meng; Dong-xia Yue; Jin-hui Ma; Fu-yun Guo; Zi-qiang Zhou; Mohib Ur Rehman; Zainab Khalid; Guan Chen; Run-qiang Zeng; Fu-meng Zhao (Journal of Mountain Science, 2021)

Descending Modulation of Spinal Itch Transmission by Primary Somatosensory Cortex - Zi-Han Wu; Han-Yu Shao; Yuan-Yuan Fu; Xiao-Bo Wu; De-Li Cao; Sheng-Xiang Yan; Wei-Lin Sha; Yong-Jing Gao; Zhi-Jun Zhang (Neuroscience Bulletin, 2021)

Devosia sediminis sp. nov., isolated from subterranean sediment - Fu Ma; Zhi-Da Zi; Wei Li; Zhao-Xuan Wang; Jun Lu; Jie Lv (Archives of Microbiology, 2021)

Role of nucleus accumbens microRNA-181a and MeCP2 in incubation of heroin craving in male rats - Wenjin Xu; Qingxiao Hong; Zi Lin; Hong Ma; Weisheng Chen; Dingding Zhuang; Huaqiang Zhu; Miaojun Lai; Dan Fu; Wenhua Zhou; Huifen Liu (Psychopharmacology, 2021)

Kelp aquaculture in China: a retrospective and future prospects - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
Globally, China has the largest scale of kelp cultivation and production operations. However, its kelp aquaculture industry is suffering from declining germplasm diversity, degradation of agronomic traits, the presence of polluted environments, changing ocean conditions and increasing anthropological interference. This review covers two of the most commercially important kelp species in China, viz. Saccharina japonica and Undaria pinnatifida . It summarizes the history of their cultivation, production, economic and ecological benefits, their breeding programmes (e.g. inter‐ and intra‐specific hybridization and marker‐assisted selection) and efforts towards population genetic diversity and conservation. The article focuses on three significant challenges, for example genetic cross‐contamination between the wild and farmed kelp populations, ocean warming and ocean acidification. Accordingly, we outline the steps required to provide several intervention measures, for example (i) collection and preservation of wild and cultivated kelp germplasm; (ii) selection of suitable cultivation sites under changing environmental conditions; (iii) developing stress‐resistant cultivars; and finally, (iv) adoption of innovative cultivation models. The review concludes with genome‐based, designs for molecular breeding and calls for the establishment of an East Asian Kelp Consortium (EAKC). Collectively, the Chinese kelp industry could provide beneficial goods and services, for example bioenergy to fine chemicals and environmental benefits, such as carbon capture, pH amelioration and provision of habitat for many other marine species of commercial value. The strategies proposed in this article thus have the potential to not only improve but also reinvigorate the kelp industry in China and nearby Japan and Korea, in the context of both environmental health and economic benefits.

Cover Image - Zi‐Min Hu; Ti‐Feng Shan; Jie Zhang; Quan‐Sheng Zhang; Alan T. Critchley; Han‐Gil Choi; Norishige Yotsukura; Fu‐Li Liu; De‐Lin Duan (Reviews in Aquaculture, 2021)
The cover image is based on the Review Article Kelp aquaculture in China: A retrospective and future prospects by Zi‐Min Hu et al., https://doi.org/10.1111/raq.12524 . image

Knockdown of Arginyl-tRNA Synthetase Attenuates Ischemia-Induced Cerebral Cortex Injury in Rats After Middle Cerebral Artery Occlusion - Yang Liu; Xue-Bin Hu; Li-Zhi Zhang; Zi Wang; Rong Fu (Translational Stroke Research, 2021)
Some researchers have previously shown that RNAi knockdown of arginyl-tRNA synthetase (ArgRS) before or after a hypoxic injury can rescue animals from death, based on the model organism, C. elegans . However, there has been no study on the application of arginyl-tRNA synthetase knockdown in treating mammalian ischemic stroke, and its potential mechanism and effect on ischemic brain damage are still unknown. Here, we focused on the Rars gene, which encodes an arginyl-tRNA synthetase, and examined the effects of Rars knockdown in a permanent middle cerebral artery occlusion model in rats. To achieve this aim, adult male Sprague-Dawley (SD) rats were given right cerebral cortex injections of short hairpin RNA (shRNA) adenovirus (AV) particles to knock down arginyl-tRNA synthetase, and a non-targeting control (NTC) vector or phosphate-buffered solution served as the controls. After 4 days, the rats were exposed to permanent middle cerebral artery occlusion (pMCAO). Then, the right cerebral cortex level of arginyl-tRNA synthetase was examined, and the effects of the Rars knockdown were evaluated by differences in infarction volume, oxidative stress, blood-brain barrier, mitochondrial function, and glucose metabolism at 1 day and 3 days after MCAO. The injection of shRNA adenovirus particles successfully suppressed the expression of arginyl-tRNA synthetase in the cerebral cortex. We observed an improvement in oxidative stress, mitochondrial function, and glucose utilization and a reduction in brain edema compared with the non-targeting control rats with suppressed expression of arginyl-tRNA synthetase mRNA in the ipsilateral ischemic cortex of the brain. Our findings indicate that knockdown of arginyl-tRNA synthetase in the cerebral cortex exerted neuroprotective effects, which were achieved not only by the improvement of oxidative stress and glucose utilization but also by the maintenance of mitochondrial morphological integrity and the preservation of mitochondrial function. Knockdown of ArgRS administration could be a promising approach to protect ischemic stroke.

Key statistical characteristics of the mesoscale convective systems generated over the Tibetan Plateau and their relationship to precipitation and southwest vortices - Zi Mai; Shen‐Ming Fu; Jian‐Hua Sun; Liang Hu; Xiu‐ming Wang (International Journal of Climatology, 2021)
Based on hourly geostationary satellite temperature‐of‐black‐body data, 9,754 mesoscale convective systems (MCSs) are found to form over the Tibetan Plateau (TP) during 16 warm seasons. In the whole study period, neither the occurrence numbers of these MCSs nor their other key characteristics are found to have a significant trend of increasing/decreasing. The MCSs can form anywhere over the TP, and ~6.6% of them can move eastward and vacate the TP (defined as the eastward‐moving type [EMT]). The EMTs' mean occurrence frequency and lifespan are ~0.3 per day and ~12.0 hr, respectively. Compared to the MCSs that do not vacate the TP, the EMTs usually have stronger intensity, longer lifespan, and develop more rapidly but generate in a drier environment. The vacating stage of an EMT usually begins in the latter half of its lifespan, and an EMT tends to reach its maximum cloud area when it is about to vacate the TP. After vacating the TP, an EMT usually weakens at first and then enhances again. Vorticity budget indicates that the convergence‐related horizontal shrinking and the convection‐related vertical vorticity transport govern the cyclonic‐vorticity increase/maintenance associated with the longer‐lived EMTs. Of all the EMTs, only ~8% are associated with southwest vortices (SWVs), and the precipitation related to these EMTs contributes ~20% to the local hourly heavy precipitation. Compared to the EMTs that are not related to SWVs, those that are generally vacate the TP sooner, last longer having vacated the TP, and have longer whole lifespans.

Reversal of Social Recognition Deficit in Adult Mice with MECP2 Duplication via Normalization of MeCP2 in the Medial Prefrontal Cortex - Bin Yu; Bo Yuan; Jian-Kun Dai; Tian-lin Cheng; Sheng-Nan Xia; Ling-Jie He; Yi-Ting Yuan; Yue-Fang Zhang; Hua-Tai Xu; Fu-Qiang Xu; Zhi-Feng Liang; Zi-Long Qiu (Neuroscience Bulletin, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Possible aerosol transmission of COVID-19 and special precautions in dentistry - Zi-yu Ge; Lu-ming Yang; Jia-jia Xia; Xiao-hui Fu; Yan-zhen Zhang (Journal of Zhejiang University-SCIENCE B, 2020)

Numerical simulation study of strip filling for water-preserved coal mining - Wei Bo Sun; Yan Wang; Hua Fu Qiu; Zi Wei Ding (Environmental Science and Pollution Research, 2020)

Programmed cell death induced by cadmium stress and/or boron deprivation in tobacco (Nicotiana tabacum L.) cultivar Bright Yellow 2 cells - Li Ping Jiang; Lin Zi; Xiao Fang Liu; Zi-Xi Liu; Lai Fu Zhong; Xiang Xin Xue (In Vitro Cellular & Developmental Biology - Plant, 2019)

Amplitude- and duration-sensitivity of single-on and double-on neurons to CF-FM stimuli in inferior colliculus of Pratt’s roundleaf bat (Hipposideros pratti) - Ming-Jian Yang; Kang Peng; Jing Wang; Jia Tang; Zi-Ying Fu; Xin Wang; Qi-Cai Chen (Journal of Comparative Physiology A, 2018)

Microarray expression profiling and co-expression network analysis of circulating LncRNAs and mRNAs associated with neurotoxicity induced by BPA - Wei Pang; Fu-Zhi Lian; Xue Leng; Shu-min Wang; Yi-bo Li; Zi-yu Wang; Kai-ren Li; Zhi-xian Gao; Yu-gang Jiang (Environmental Science and Pollution Research, 2018)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Wnt5a mediated canonical Wnt signaling pathway activation in orthodontic tooth movement: possible role in the tension force-induced bone formation - Hai-Di Fu; Bei-Ke Wang; Zi-Qiu Wan; Heng Lin; Mao-Lin Chang; Guang-Li Han (Journal of Molecular Histology, 2016)

Gelatin Nanostructured Lipid Carriers Incorporating Nerve Growth Factor Inhibit Endoplasmic Reticulum Stress-Induced Apoptosis and Improve Recovery in Spinal Cord Injury - Si-Pin Zhu; Zhou-Guang Wang; Ying-Zheng Zhao; Jiang Wu; Hong-Xue Shi; Li-Bing Ye; Fen-Zan Wu; Yi Cheng; Hong-Yu Zhang; Songbin He; Xiaojie Wei; Xiao-Bing Fu; et al. (Molecular Neurobiology, 2016)

A new plant assemblage from the Middle Triassic volcanic tuffs of Pingchuan, Gansu, northwestern China and its paleoenvironmental significance - Fu-Jun Ma; Qiu-Jun Wang; Jun-Ling Dong; Hao-Fei Wang; Zi-Xi Wang; Feng-Tai Zhang; Bai-Nian Sun (PalZ, 2016)

Effect of echolocation behavior-related constant frequency–frequency modulation sound on the frequency tuning of inferior collicular neurons in Hipposideros armiger - Jia Tang; Zi-Ying Fu; Chen-Xue Wei; Qi-Cai Chen (Journal of Comparative Physiology A, 2015)

Geochronology and provenance of detrital zircons from late Palaeozoic strata of central Jilin Province, Northeast China: implications for the tectonic evolution of the eastern Central Asian Orogenic Belt - Zi-Jin Wang; Wen-Liang Xu; Fu-Ping Pei; Zhi-Wei Wang; Yu Li (International Geology Review, 2015)

Complex seismic wavefield interpolation based on the Bregman iteration method in the sparse transform domain - Fu-Yan Gou; Cai Liu; Yang Liu; Xuan Feng; Fang-Zi Cui (Applied Geophysics, 2014)

Emodin elicits cytotoxicity in human lung adenocarcinoma A549 cells through inducing apoptosis - Wing-Yan Li; Yam-Fung Ng; Huan Zhang; Zi-Dong Guo; De-Jian Guo; Yiu-Wa Kwan; George Pak-Heng Leung; Simon Ming-Yuen Lee; Peter Hoi-Fu Yu; Shun-Wan Chan (Inflammopharmacology, 2014)

Regulation of Autophagy and Ubiquitinated Protein Accumulation by bFGF Promotes Functional Recovery and Neural Protection in a Rat Model of Spinal Cord Injury - Hong-Yu Zhang; Zhou-Guang Wang; Fen-Zan Wu; Xiao-Xia Kong; Jie Yang; Bei-Bei Lin; Shi-Ping Zhu; Li Lin; Chao-Shi Gan; Xiao-Bing Fu; Xiao-Kun Li; Hua-Zi Xu; et al. (Molecular Neurobiology, 2013)

Local neuronal circuits that may shape the discharge patterns of inferior collicular neurons - Zi-Ying Fu; Hui-Xian Mei; Liang Cheng; Jing Bai; Jia Tang; Philip Hung-Sun Jen; Qi-Cai Chen (Neuroscience Bulletin, 2013)

Overexpression of TFAM Protects 3T3-L1 Adipocytes from NYGGF4 (PID1) Overexpression-Induced Insulin Resistance and Mitochondrial Dysfunction - Chun-Mei Shi; Guang-Feng Xu; Lei Yang; Zi-Yi Fu; Ling Chen; Hai-Long Fu; Ya-Hui Shen; Lu Zhu; Chen-Bo Ji; Xi-Rong Guo (Cell Biochemistry and Biophysics, 2013)

The analysis on IP signals in TEM response based on SVD - Chuan-Tao Yu; Hong-Fu Liu; Xin-Jun Zhang; De-Yi Yang; Zi-Hong Li (Applied Geophysics, 2013)

Nicardipine in the treatment of aneurysmal subarachnoid haemorrhage: a meta-analysis of published data - Ren-qiang Huang; Fu-gang Jiang; Zi-min Feng; Tian-yi Wang (Acta Neurologica Belgica, 2013)

Association of interleukin-1 gene polymorphisms with multiple sclerosis: a meta-analysis - Jian Huang; Zi-Kang Xie; Rong-Bin Lu; Zheng-Fu Xie (Inflammation Research, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Dong Niu; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Secretory expression of K88 (F4) fimbrial adhesin FaeG by recombinant Lactococcus lactis for oral vaccination and its protective immune response in mice - Chun Xia Hu; Zi Rong Xu; Wei Fen Li; Niu Dong; Ping Lu; Ling Lin Fu (Biotechnology Letters, 2009)

Identification, expression and tissue distribution of a renalase homologue from mouse - Jian Wang; Shaoling Qi; Wei Cheng; Li Li; Fu Wang; Ying-Zi Li; Shu-Ping Zhang (Molecular Biology Reports, 2008)

High-Level Secretion of a Chimeric Thermostable Lichenase from Bacillus subtilis by Screening of Site-Mutated Signal Peptides with Structural Alterations - Ling-lin Fu; Zi-rong Xu; Jiang-bing Shuai; Chun-xia Hu; Wei Dai; Wei-fen Li (Current Microbiology, 2008)

Genetic analysis for brix weight per stool and its component traits in sugarcane (Saccharum officinarum) - Gui-fu Liu; Hong-kai Zhou; Han Hu; Zi-hong Zhu; Yousaf Hayat; Hai-ming Xu; Jian Yang (Journal of Zhejiang University-SCIENCE B, 2007)

Relationships between O isotope equilibrium, mineral alteration and Rb–Sr chronometric validity in granitoids: implications for determination of cooling rate - Jiang Feng Chen; Yong-Fei Zheng; Zi-Fu Zhao; Bo Li; Zhi Xie; Bing Gong; Hui Qian (Contributions to Mineralogy and Petrology, 2007)

Origin of a large breccia-vein system in the Sanerlin uranium deposit, southern China: a reinterpretation - Jian-Wei Li; Mei-Fu Zhou; Xian-Fu Li; Zi-Jin Li; Zhao-Ren Fu (Mineralium Deposita, 2002)